Implementing homeland security for enterprise IT - Erbschloe, Michael (Boston : Digital Press, 2004)
This book shows what IT in organizations need to accomplish to implement The National Strategy for the Physical Protection of Critical Infrastructures and Key Assets and The National Strategy to Secure Cyberspace which were developed by the Department of Homeland Security after the terrorist attacks of September 2001. The September 11, 2001, attacks illustrated the immense vulnerability to terrorist threats. Since then there have been considerable efforts to develop plans and methods to protect critical infrastructures and key assets. The government at all levels, private sector organizations, as well as concerned citizens have begun to establish partnerships and to develop action plans. But there are many questions yet to be answered about what organizations should actual do to protect their assets and their people while participating in national efforts to improve security. This book provides practical steps that IT managers in all organizations and sectors can take to move security from the planning process into practice. *A one-minute manager approach to issuesp provides background and explanations in all areas *Step-by-step instructions on how to accomplish objectives guide readers through processes *Easy to implement advice allows readers to take quick action.
Organizing homeland security efforts -- Cross-sector security priorities and issues -- Security and critical infrastructures -- Information sharing for protecting national assets -- Homeland security initiatives by sector -- Why a national strategy to secure cyberspace is important -- Participating in a national cyberspace security response system -- Participating in a national threat and vulnerability reduction program -- Launching a national cyberspace security awareness and training program -- Working to secure governments' cyberspace -- Global cyberspace security cooperation -- Moving into the future.
Title from book cover on Web Page (viewed Oct. 26, 2005).
Includes bibliographical references and index.
May be limited to subscribing institutions.
Keywords: Computer security; Internet -- Security measures; Computer networks -- Security measures; Cyberterrorism; Electronic books